2004
DOI: 10.1080/07315724.2004.10719409
|View full text |Cite
|
Sign up to set email alerts
|

Changes in USDA Food Composition Data for 43 Garden Crops, 1950 to 1999

Abstract: We suggest that any real declines are generally most easily explained by changes in cultivated varieties between 1950 and 1999, in which there may be trade-offs between yield and nutrient content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
212
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(227 citation statements)
references
References 30 publications
5
212
0
10
Order By: Relevance
“…Recent estimates indicate that nearly half of the world's population suffers from Zn deficiency (Cakmak 2007), while more than two billion people worldwide are anaemic and much of it is due to Fe deficiency (Anonymous 2001). It has been assumed that increase in yield has resulted in decrease in the content of mineral elements due to a "dilution effect" caused by both environmental and genetic factors (Jarrel and Beverly 1981, Davis et al 2004, Davis 2005, White et al 2009). Furthermore, the recent studies have indicated that high yielding genotypes have lower minerals content (Monasterio and Graham 2000, Davis et al 2004, Garvin et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates indicate that nearly half of the world's population suffers from Zn deficiency (Cakmak 2007), while more than two billion people worldwide are anaemic and much of it is due to Fe deficiency (Anonymous 2001). It has been assumed that increase in yield has resulted in decrease in the content of mineral elements due to a "dilution effect" caused by both environmental and genetic factors (Jarrel and Beverly 1981, Davis et al 2004, Davis 2005, White et al 2009). Furthermore, the recent studies have indicated that high yielding genotypes have lower minerals content (Monasterio and Graham 2000, Davis et al 2004, Garvin et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lombard et al (2005) examined the total flavonol content in 5 onion varieties and found significantly higher concentrations in red skinned onion varieties compared to yellow varieties [37]. In a detailed study of 75 onion cultivars levels of quercetin were higher in red, pink and yellow onions (in the range 54 -286 mg/kg FW) whilst white onions contained only trace amounts of quercetin [130].…”
Section: Crop and Cultivarmentioning
confidence: 99%
“…Studies document differences in flavor as foods age (Gray, Gomaa, & Buckley, 1996;Kader, 2008), as well as for meats and dairy produced from pastured animals versus others (Urbach, 1990;Priolo, Micol, & Agabriel, 2001). Additionally, cultivar selection has shifted over time from those chosen for flavor or nutrition, to those that can produce the highest yield or that are most resilient to the time and physical requirements of the modern food distribution system (Davis, Epp, & Riordan, 2004). Second, it is notable that the older adults focused much of their discussion of changed food taste on meats, seconded by fruits; if their senses of taste had changed, presumably this would affect their perceptions of all foods.…”
Section: Older Adults and The Flavor Of Modern Foodmentioning
confidence: 99%